2021
DOI: 10.3906/zoo-2103-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of silymarin on oxidative DNA damage and inflammatory markers in ischemia/reperfusion injury following experimental testicular torsion/detorsion in rats

Abstract: The aim of the present study was to clarify the effects of silymarin on experimental testicular ischemia / reperfusion injury. A total of 40 Wistar albino rats (10-12 weeks of age weighing 280-300 grams) were randomly divided into five groups.Control group: No surgical procedures were performed. Torsion 3 h / detorsion 3 h group; torsion 3 h / detorsion 24 h group; torsion 3 h / detorsion 3 h + silymarin (250 mg/kg) group; and torsion 3 h / detorsion 24 h + silymarin (250 mg/kg) group. In the study, 720 ° tors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Our results are in agreement with other studies which have reported the reduction of serum testosterone levels in the torsion/detorsion process. Belhan et al reported in their study that testicular ischemia/reperfusion led to 7 Andrologia testis tissue damage and reduction in serum testosterone level [32].…”
Section: Discussionmentioning
confidence: 94%
“…Our results are in agreement with other studies which have reported the reduction of serum testosterone levels in the torsion/detorsion process. Belhan et al reported in their study that testicular ischemia/reperfusion led to 7 Andrologia testis tissue damage and reduction in serum testosterone level [32].…”
Section: Discussionmentioning
confidence: 94%